RETAIL STRATEGIES OF NOTTINGHAM FOREST FOOTBALL CLUB - Dube, Nipun; Onwuka, Ngozi; Vig, Tarun (2008)
As football fans and also business students with particular interest in retail strategy, the opportunity to work with Nottingham Forest in that capacity was appropriate. Nottingham Forest Football Club is concerned with the level of sales and revenue it makes from merchandise sales, across all retail channels. In tackling this issue, it was important to understand the shift in football from being just about entertainment but more about a business which not only pays for itself but also makes profit. Key to this shift is the knowledge that although football's (and sports in general) offering is intangible (i.e. it provides entertainment and a sense of belonging and attachment); it is this very intangibility that provides the basis for tangible cues. Tangible cues are physical signs and signals use to represent or direct to a non tangible service. The success of these tangible cues is dependent on the value attached to the club by the fans; that is, the loyalty of the fans to the brand. It was also pertinent to note that in retailing, it is important to incorporate the various channels available. Most effective retail organizations have incorporated successful multi-channel retailing. These channels include the retail store, the online store, catalogues and telephone. If any of the channels is viewed uncharitably by customers (in this case the fans), it could and does affect the rest of the channels. Channel conflict is not tolerable in present day retail strategy. Based on these, the report will serve to explore how NFFC can address issues like capitalizing on the brand Nottingham Forest which is very pertinent when looking how to utilize multi-channel retailing. Staffing is also an important aspect for any retailer which is trying to improve on its sales, which have been addressed in the report. The outlined issues should prove useful in finding out the key problem areas and then making recommendations based on and this research was able to locate areas that needed addressing. These include the store quantity and locations, the brand leveraging and the various partnership deals, employee motivation and multi channel retailing strategies.